Bentuk Penguatan Pendidikan Karakter pada Peserta Didik dengan Penerapan Reward dan Punishment - Karine Rizkita; Bagus Rachmad Saputra (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The writing of this article aimed to (1) support the giving and punishment of students' learning motivation, (2) discuss indicators of students who get prizes and penalties. This research was conducted using a qualitative descriptive method to obtain facts in the field about the form of increasing character education in students with the application of gifts and penalties. Researchers conducted field studies and conducted interviews with and conducted documentation studies at SMP Negeri 1 Bojonegoro as a research location. The results of the research found by researchers at SMP Negeri 1 Bojonegoro are as follows: (1) the application of rewards and punishments to the learning motivation of students at SMP Negeri 1 Bojonegoro, (2) any indicators giving of gift and punishment